2022
DOI: 10.31083/j.rcm2302049
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome and renal impairment: a systematic review

Abstract: Background: Coronary artery disease (CAD) and chronic kidney disease (CKD) may reciprocally influence each other. Patients with CAD and CKD have an increased risk of both ischemic and hemorrhagic events. Methods: In the present review, we summarize the existing literature focusing on the relationship between kidney dysfunction and acute coronary syndromes (ACS) in terms of risk factors, complications, and prognosis. We discuss also about the best evidence-based strategies to prevent deterioration of renal func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Heart and kidney injuries can cause each other and the superposition of injuries is amplified. 35 , 36 As serum creatinine levels are the most commonly used measure of kidney function, it may have an influential impact on cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Heart and kidney injuries can cause each other and the superposition of injuries is amplified. 35 , 36 As serum creatinine levels are the most commonly used measure of kidney function, it may have an influential impact on cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney diseases patients have a higher risk of ischemia and AMI and a worse prognosis, especially in dialysis patients. Both cardiac and renal insufficiency can aggravate the prognosis and lead to disease progression [ 28 ]. Type 2 diabetes is another critical factor, increasing the risk of major adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of chronic kidney injury which is known to increase cardiovascular events for many reasons, such as chronic inflammation, oxidative stress, endothelial dysfunction, and calcification increases up to 20%-25% in ACS patients. [9,10] As suggested by these findings, CAD is often accompanied by anemia and impaired renal function. This association, which is frequently seen in patients with ACS, has been evaluated in studies, and a relationship has been shown of anemia and impaired renal function with increased early and long-term mortality and adverse outcomes in patients with ACS.…”
Section: Demir Et Al • Medicine (2023) 102:41mentioning
confidence: 90%
“…The frequency of chronic kidney injury which is known to increase cardiovascular events for many reasons, such as chronic inflammation, oxidative stress, endothelial dysfunction, and calcification increases up to 20%-25% in ACS patients. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%